The methyltransferase METTL16 in digestive system cancers: functions and mechanisms - Li, Jia; Bao, Yueyuan; Yao, Fei; Wu, Qingming (Frontiers in Oncology, 2026)
N6-methyladenosine (m6A) methylation, the most prevalent mRNA modification, affects RNA transcription, splicing, and stability. Methyltransferase-like 16 (METTL16), a novel m6A methyltransferase, regulates the expression of target mRNAs via m6A-mediated modifications. The methyltransferase domain of METTL16 is essential for its catalytic activity. In addition to acting as a methyltransferase, METTL16 can also facilitate mRNA translation in an m6A-independent manner, thus regulating cancer development and progression. Accumulating evidence has indicated that METTL16 plays a pivotal role in the progression of various cancers by regulating cell proliferation, apoptosis, metastasis, and resistance to chemotherapy. In this review, we provide a narrative review of the functions of METTL16 and summarize its oncogenic and tumor-suppressive functions as well as its underlying mechanisms in human digestive system cancers. However, further in-depth studies are required to validate these findings. By comprehensively summarizing the current literature on METTL16, we provide a theoretical basis for its application as a diagnostic and prognostic marker as well as a potential therapeutic target for digestive system cancers.